Mincle and STING-Stimulating Adjuvants Elicit Robust Cellular Immunity and Drive Long-Lasting Memory Responses in a Foot-and-Mouth Disease Vaccine - Lee, Min Ja; Jo, Hyundong; Shin, Sung Ho; Kim, Su-Mi; Kim, Byounghan; Shim, Hang Sub; Park, Jong-Hyeon (Frontiers in Immunology, 2019)
Conventional foot-and-mouth disease (FMD) vaccines have several limitations, such as slow induction of the antibody, short persistence of antibody titers, and low vaccine efficacy and safety in pigs. Despite the importance of the cellular immune response in the host defense at the early stages of foot-and-mouth disease virus (FMDV) infection, most FMD vaccines focus on humoral immune responses. Antibody responses alone are not sufficient to drive complete protection against FMDV infection, and cellular immunity is also required. From these perspectives, it is necessary to develop a new strategy for a novel FMD vaccine to induce a more potent cellular immune response and a long-lasting immune response as well as to address safety. Previously, we demonstrated the potential of various pattern recognition receptor (PRR) ligands and cytokines as adjuvants for the FMD vaccine. Based on these results, we investigated PRR ligands and a cytokine adjuvant-mediated memory response in mice and the cellular immune response in peripheral blood mononuclear cells (PBMCs) isolated from cattle and pigs. We further evaluated target-specific adjuvants, including Mincle, STING, TLR-7/8, and Dectin-1/2 ligand, for their role in generating ligand-mediated, long-lasting memory responses in cattle and pigs. The combination of the Mincle and STING-stimulating ligands, i.e., trehalose-6, 6’dibehenate (TDB) and bis-(3’-5’)-cyclic dimeric guanosine monophosphate (c-di-GMP), induced a high level of antigen-specific and virus-neutralizing antibody titers at the early stage of vaccination and maintained the long-lasting memory immune response in pigs. These findings will provide important clues for the development of a robust FMD vaccine that will stimulate both cellular and humoral immune responses to elicit a long-lasting, effective immune response and address the limitations of the current FMD vaccine.